If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -50 = 62 Reorder the terms: -50 + 4x = 62 Solving -50 + 4x = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '50' to each side of the equation. -50 + 50 + 4x = 62 + 50 Combine like terms: -50 + 50 = 0 0 + 4x = 62 + 50 4x = 62 + 50 Combine like terms: 62 + 50 = 112 4x = 112 Divide each side by '4'. x = 28 Simplifying x = 28
| ((x-118.75)/118,75)*100-4=0 | | 8y=2.56 | | 27=6+c | | 5x-7+3x=2x+5 | | 7.68=3w | | 15+11=26 | | X/3-6=14 | | 6/3+3/7 | | P-2=-1/2 | | (2g^2+3x)dx+2+gdy=0 | | 4x+20=4(x-5) | | 3.2=u | | 4v=5.12 | | (9x+5)(2x^2-5x-3)=0 | | 3(-2-4x)=2(2+b) | | 2x-3+6x-8=4+2x | | -3y+7x=15 | | (2g^2+3x)dx+2xgdy=0 | | 3/6+3/7 | | 5/x+6=10 | | -6+b=-18 | | 3x+2(7x-11)=131 | | 3(-16+4x)=-24 | | 6x+2=4x+16 | | 88-6x=39x+23x | | a^2-2a-8= | | -1-5z-7+12z=z+z+15+z+1 | | 5x+5=3x+35 | | 2/5g+2 | | -4/9n=8 | | y=37.4296+4.99 | | X-2(x-6)=-x+12 |